KEPUASAN KERJA SEBAGAI PEMODERASI PENGARUH INDEPENDENSI DAN AKUNTABILITAS PADA KUALITAS AUDIT DI KAP PROVINSI BALI - Apriliani, Luh Mas Gia; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 20 No 3 (2017), 2017)
Good audit quality is to be achieved auditors. Based SPAP auditor conducted audit quality is said, if they meet the conditions or auditing standards. Such provisions require that auditors be independent and accountability. This study aims to examine the effect of independence and accountability of the audit quality and to test whether job satisfaction moderate the influence of the independence and accountability of the audit quality. The study was conducted at the KAP in the province of Bali. Samples were selected using purposive sampling technique. Data obtained through questionnaires and data analysis technique used is multiple linear regression and MRA. Based on the analysis, it is known that that independence and accountability positive effect on audit quality. Job satisfaction able to moderate influence on the independence of audit quality but are not able to moderate the influence of accountability on the quality of the audit.
Keywords: Job satisfaction, independence, accountability, quality of audits.